Graphic Design - Krasimira Drumeva (Convergências - Revista de Investigação e Ensino das Artes)
In the genesis of his existence, man had an experiential need to explore the world around and to communicate with his fellows in order to survive and continue the kin. The need for social connections provoked the development and improvement of verbal and non-verbal communication. All the knowledge of humanity is transmitted and stored through language, writing, behaviour and images. Due to the specific nature of human perceptions, non-verbal means of interaction are much more effective and natural. For these reasons, graphic design, as a means of visual communication, widely applies a non-verbal presentation of content through images and symbols to reach a wide audience. This article aims to explore the application of images, which already carry much more complex meanings, in the process of sharing information. The focus of research is the process of interaction between the images applied in graphic design and the context, and their transformation into symbols. The article explores the interpretation of symbols, which are given much more qualitative characteristics in order to build on new ideas that the process of content visualization requires.